Anterior uveitis in patients with spondyloarthritis treated with secukinumab or tumour necrosis factor inhibitors in routine care: does the choice of biological therapy matter?. Issue 11 (15th June 2021) - Lindström, Ulf; Bengtsson, Karin; Olofsson, Tor; Di Giuseppe, Daniela; Glintborg, Bente; Forsblad-d'Elia, Helena; Jacobsson, Lennart T H; Askling, Johan
Abstract : Background: The effect of interleukin 17-inhibitors on anterior uveitis (AU) in spondyloarthritis (SpA) is poorly understood. This study aimed to compare the risk of AU during treatment with secukinumab versus tumour necrosis factor inhibitors (TNFi). Methods: Patients with SpA starting secukinumab or a TNFi 2015 through 2018 were identified in the Swedish Rheumatology Quality Register. Occurrence of AU was identified based on diagnosis codes in outpatient ophthalmology care in the National Patient Register. The main outcomes were crude rates of AU-diagnoses per 100 patient-years, and adjusted HRs for AU, during treatment, in patients without AU during the year before treatment start (in order to reduce confounding by indication). HRs were adjusted for age, sex, history of AU and patient global assessment of disease activity. Results: Based on 4851 treatment starts (456 secukinumab; 4395 any TNFi), the rate of AU-diagnoses per 100 patient-years was 6.8 (95% CI 5.2 to 8.7) for secukinumab. Among the TNFi, the rate varied from 2.9 (95% CI 2.1 to 3.7) for infliximab and 4.0 (95% CI 3.3 to 4.9) for adalimumab to 7.5 (95% CI 6.7 to 8.4) for etanercept. The adjusted HRs for first AU (adalimumab as reference) were: secukinumab 2.32 (95% CI 1.16 to 4.63), infliximab 0.99 (95% CI 0.49 to 1.96), etanercept 1.82 (95% CI 1.13 to 2.93), golimumab 1.59 (95% CI 0.90 to 2.80) and certolizumab 1.12 (95% CI 0.44 to 2.83). Sensitivity analyses confirmed the pattern of higher AU rates with secukinumab and etanercept versus monoclonal TNFi. Conclusion: As used in clinical practice in SpA, secukinumab appears to be associated with a higher risk of AU, compared with the monoclonal TNFi and a similar risk compared with etanercept.